A combination of spearmint and flaxseed extract improved endocrine and histomorphology of ovary in experimental PCOS - Mina Mehraban; Gholamali Jelodar; Farhad Rahmanifar (BMC, 2020)
Abstract Background Polycystic ovary syndrome (PCOS) is a complex reproduction and endocrine disorder of women in the reproductive age. Spearmint (Mentha spicata L.) has anti-androgenic activity and flaxseed (Linum usitatissimum L.) contains phytoestrogen and was reported to improve PCOS conditions. This study aimed to evaluate PCOS conditions following administration of a mixture of these two plants. Methods Twenty-four rats with regular cycles were randomly divided into four groups as control (C) and treatment-control (TC) received a combination of spearmint extract (SE) + flaxseed extract (FE). PCOS was induced in PCOS and treatment (T) groups by a single intramuscular injection of estradiol valerate. The treatment group received a combination of SE and FE for 30 days, 7 weeks after injection of estradiol valerate. Estrous cycles were monitored for 10 days and in the last day animals were sacrificed, ovaries were collected for the histomorphometric study and the serum levels of progesterone, testosterone, estradiol, and dehydroepiandrosterone (DHEA) were measured. Result Significant rise in progesterone and a decrease in testosterone and estradiol with no significant change of DHEA in the T group, was observed in comparison with the PCOS group (P < 0.05). No significant difference noticed between T and control groups (C &CT) regarding evaluated hormones. A significant increase in primary, pre-antral and antral follicles noticed in the T group compared to the PCOS group. The number of cystic follicles decreased in the T group compared with the PCOS group. Granulosa layer thickness increased while the thickness of theca decreased significantly in the T group compared to the PCOS group (P < 0.05). No significant endocrine or histological differences noticed between C and TC groups. Conclusion A combination of flaxseed and spearmint extract improved the endocrine profile and the histomorphometric features of the ovary in the T group compared to the PCOS group.